Why Hedge? - A Critical Review of Theory and Empirical Evidence - - Norbert Ammon (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
Finance theory does not provide a comprehensive framework for explaining risk management within the imperfect financial environment in which firms operate. Corporate managers, however, rank risk management as one of their most important objectives. Therefore, it is not surprising that papers on the question why firms hedge are mushrooming. This paper critically reviews this literature and analyses the implications for risk management practice. It is distinguished between two competing approaches to corporate hedging: equity value maximising strategies and strategies determined by managerial risk aversion. The first category suggests that managers act in the best interest of shareholders. They hedge to reduce real costs like taxes, costs of financial distress and costs of external finance or to replace home-made hedging by shareholders. The second category considers that managers maximise their personal utility rather than the market value of equity. Their hedging strategy, therefore, is determined by their compensation plan and reputational concerns. There is ambiguous empirical evidence on the dominant hedging motive. It depends on the environment in which firms operate (e.g. tax schedule) and on firm characteristics (e.g. capital intensity). In general, one can observe that (i) hedging taxable income is of minor importance, (ii) firms with a high probability of financial distress hedge more, (iii) companies with greater growth opportunities hedge more, (iv) managers with common stockholdings hedge more than managers with option holdings and (v) high ability managers hedge more than low ability managers. The total benefits of hedging are not the sum across the various motives. Therefore, a manager has to concentrate on a primary motive to implement an effective risk management programme: If his primary motive is to minimise corporate taxes, he will hedge taxable income. If his primary concern is to reduce the costs of financial distress and if he can faithfully communicate the firm?s true probability of default, his hedging strategy will focus on the market value of debt and equity. If hedging is prompted to reduce the demand for costly external finance, he will hedge cash flows. If the manager is concerned with his reputation, he will focus on accounting earnings. Once he has focused on a certain exposure, the manager has to decide whether he wants to minimise the volatility of this exposure or simply avoid large losses. – – Der Artikel gibt einen Literaturüberblick zur Fragestellung, warum Unternehmen Risikomanagement betreiben und analysiert die Umsetzung in der Unternehmenspraxis. Ausgehend von den Irrelevanzthesen von Modigliani/Miller wird gezeigt, daß die starke Betonung des Risikomanagements in Unternehmen auf zweierlei Arten erklärbar ist: Zum einen erhöht Hedging den Shareholder Value, da es Steuern, Bankrottkosten, die Kosten von externem Kapital und den Absicherungsbedarf von schlecht diversifizierten Aktionären verringern kann. Zum anderen kann Hedging den Nutzen von Managern erhöhen, soweit es einen Einfluß auf deren Vermögen oder Ruf hat. Was die Umsetzung der Hedging-Ziele in die Unternehmenspraxis anbetrifft, haben die Modelle unterschiedliche Konsequenzen bezüglich der Art und des Ausmaßes des abzusichernden Risikos.
Keywords: 330; Risk Management; Hedging; Agency Theory; Shareholder Value; Risikomanagement; Hedging; Theorie der Unternehmung; Agency Theory; Shareholder Value; Theorie; Welt